The Relationship between Religion and Science - Indo Santalia (JICSA : Journal of Islamic Civilization in Southeast Asian, 2015)
Before rapid developments of science, as we see and experience today, religion - related to beliefs, ideas, institutions, worship, social action, laws and norms, tools, and a holy book as its source – has been exist with its various plural forms. Followers of religion agree that the follower community retained, adhered to, and maintained spiritual values and life norms through creed, belief or faith, ritual worship, and certain habits. Inheritance of religious values through continuous living tradition across generation is a sign movement of religious traditions and culture by humankind since centuries ago. When there is a civilization, a religion will always follow it.